(3GdWQjbI GdeMeOjI hGdSjQI GdCMeOjIs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEf GdYbd hGdfbd eJhGabGf hGdcJGH hGdSfI eJWGHbGf Cf GdOfjG aGfjI SQjYI GdRhGd hGdNQGH YRgG Pd hfYegG fbe hTQGFgG SQGH hCf GdOGQ GdBNQI gj GdMjhGf CYOJ ddeJbjf ef Cgd GdEjeGf (B...s
(3BNQgG (B:s
... (3GdaUd GdKGdK aj CehQ eHJOYI HGWdI CcH GdfGS YdjgG Ydi Xf CfgG bQH ebUhOI hgPg cKjQI adfPcQ CYXegG efgG hb(B5(3aGdChbGa jJjeG GdfbhO dJdGhI GdbQBf GdYXje Ch dCf jUdj fhGad Ch dGf jSHM dGf jgdd hjUdj (B.. (3hfbhd GdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\61s
(3gOjI GdYGQajf (B2\252s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs